Low-Noise 3-D Avalanche Photodiodes - Zhiwei Wu; Jingshu Guo; Yuan Li; Yanli Zhao (IEEE Photonics Journal)
In this paper, we present a new 3-D structure for the InP-based avalanche photodiode, aiming at decreasing the excess noise factor. To the best of our knowledge, it is the first time new device designs based on the recently developed 3-D spatial dead space model in 2014 have been proposed. In addition, we also propose a methodology, i.e., the 2-D planar absorption distribution projection technique, for further optimizing the 3-D model. According to our theoretical simulation results, by combining photonic crystal and selective area doping, the effective k values of InP and In0.52Al0.48As can be reduced to as low as ∼0.19 and as ∼0.13, respectively. Meanwhile, the optimal thickness of the multiplication region is larger than 0.45 $μ\text{m}$ , which reduces the tunneling effect. The detailed parameter optimization process, including optics, electronics, and material, is comprehensively presented. The examples in this paper also provide a fresh idea for researchers to foretell and design new photodetectors with the 3-D structure.